Selected Works of E. L. Lehmann 2011
DOI: 10.1007/978-1-4614-1412-4_10
|View full text |Cite
|
Sign up to set email alerts
|

On a Theorem of Bahadur and Goodman

Abstract: 1. Introduction. This note is concerned with the problem of selecting the best one (or any other specified number) of several populations. It is restricted to the symmetric case where typically the observations consist of samples of equal size from the different populations. For certain families of distributions, and Bahadur and Goodman {1952) have proved that the natural selection procedure uniformly minimizes the risk among all symmetric procedures for a large class of loss functions. In Section 2 we give a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 10 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…8 In doing so, Lehmann positioned Kames's notion of a 'Gentleman Farmer' as part of a concerted Scottish Enlightenment preoccupation with agricultural improvement. 9 Neil Davidson thoroughly demonstrated that the Scottish literati 'had an ideological need to find a solution to the problems of Scottish agriculture because the mid-century saw the consolidation in their collective consciousness of a dual identity in which both the Scottish and British elements were equally significant'. 10 The mid-century circulation of Scottish instructional manuals on agricultural management echoed Lord Kames's belief that innovating agricultural production was a necessary patriotic activity.…”
mentioning
confidence: 99%
“…8 In doing so, Lehmann positioned Kames's notion of a 'Gentleman Farmer' as part of a concerted Scottish Enlightenment preoccupation with agricultural improvement. 9 Neil Davidson thoroughly demonstrated that the Scottish literati 'had an ideological need to find a solution to the problems of Scottish agriculture because the mid-century saw the consolidation in their collective consciousness of a dual identity in which both the Scottish and British elements were equally significant'. 10 The mid-century circulation of Scottish instructional manuals on agricultural management echoed Lord Kames's belief that innovating agricultural production was a necessary patriotic activity.…”
mentioning
confidence: 99%